PENGEMBANGAN BAHAN AJAR BOOKLET DIGITAL MATERI POLA LANTAI TARI JARAN KEPANG - Amabelista Permata Cinta (Joyful Learning Journal, 2023)
Abstrak Bahan ajar sangat penting digunakan dalam meningkatkan pemahaman siswa, namun guru masih kesulitan dalam mengembangkan bahan ajar. Permasalahan terkait dengan pengembangan bahan ajar terjadi di SD Negeri 2 Dermolo Kabupaten Jepara yang belum mengenalkan bahan ajar digital pada materi pola lantai tari jaran kepang. Penelitian ini bertujuan untuk mengembangkan dan mengetahui kelayakan bahan ajar booklet digital materi pola lantai tari jaran kepang di kelas V SD Negeri 2 Dermolo Kabupaten Jepara. Peneliti melakukan penelitian Ressearch and Development dengan model ADDIE. Subjek penelitian adalah 30 siswa kelas V SD Negeri 2 Dermolo Kabupaten Jepara. Teknik pengumpulan data pada penelitian yaitu wawancara, angket, dan dokumentasi. Teknik analisis data dalam penelitian menggunakan analisis data produk. Hasil penelitian menunjukkan pengembangan bahan ajar booklet digital didesain dengan bentuk portrait tampilan penuh warna dan mudah diakses siswa menggunakan perangkat komputer maupun smartphone. Bahan ajar booklet digital materi pola lantai tari jaran kepang memuat teks materi pola lantai, gambar bentuk-bentuk pola lantai, dan video tari jaran kepang. Kelayakan bahan ajar melalui penilaian ahli bahan ajar digital memperoleh 97,2% termasuk ke dalam kualifikasi sangat layak dan penilaian dari ahli materi sebesar 79,2% termasuk ke dalam kualifikasi layak. Bahan ajar booklet digital materi pola lantai tari jaran kepang layak digunakan dalam pembelajaran seni tari khususnya materi pola lantai tari jaran kepang. Teaching materials are very important to use in increasing student understanding, but teachers still have difficulties in developing teaching materials. Problems related to the development of teaching materials occurred at SD Negeri 2 Dermolo, Jepara Regency, which had not introduced digital teaching materials to the material for the jaran kepang dance floor pattern. This study aims to develop, determine the feasibility, and effectiveness of teaching materials booklet digital floor pattern material for the jaran kepang dance in class V SD Negeri 2 Dermolo, Jepara Regency. Researchers conduct research Ressearch and Development with model ADDIE. The research subjects were 30 fifth grade students at SD Negeri 2 Dermolo, Jepara Regency. Data collection techniques in research are interviews, questionnaires, tests, and documentation. Data analysis techniques in this study used product data analysis, initial data analysis by normality test and final data analysis by paired sample t-test. The results of the research show the development of teaching materials booklet digital designed with shape portrait full-color display and easily accessible by students using computers or other devices smartphone. The digital booklet teaching material for the floor pattern material for the jaran kepang dance contains of text for the floor pattern material, pictures of floor pattern shapes, and a video for the jaran kepang dance. The feasibility of teaching materials through the assessment of digital teaching materials experts obtained 97.2% included in the very proper qualification and the assessment from material experts of 79.2% was included in the proper qualification. The effectiveness of teaching materials booklet digital is known from the final student learning outcomes and test resultst-test which obtained the results of t count > t table. Shows that dance learning outcomes increase with the teaching materials booklet digital material for the jaran kepang dance floor pattern.